2008
DOI: 10.1152/ajplung.00442.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of nanoparticles with pulmonary structures and cellular responses

Abstract: Combustion-derived and synthetic nano-sized particles (NSP) have gained considerable interest among pulmonary researchers and clinicians for two main reasons. 1) Inhalation exposure to combustion-derived NSP was associated with increased pulmonary and cardiovascular morbidity and mortality as suggested by epidemiological studies. Experimental evidence has provided a mechanistic picture of the adverse health effects associated with inhalation of combustion-derived and synthetic NSP. 2) The toxicological potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(141 citation statements)
references
References 142 publications
(147 reference statements)
0
138
1
2
Order By: Relevance
“…Indeed among all potential portals of entering the human body, the respiratory system is the most susceptible to particle invasion due to its large surface area in direct contact with the environment. 14 With their small size, a large portion of inhaled NPs can penetrate the respiratory tracts and deposit in the deep lung, where the NPs first interact with the pulmonary surfactant (PS) lining layer of alveoli and develop the so-called PS biomolecular corona. 15−17 The PS is composed of approximately 90% lipids, including various phospholipids and cholesterol, and 10% proteins (named SP-A, SP-B, SP-C, and SP-D) by weight.…”
Section: U Nderstanding Interactions Between Nanoparticlesmentioning
confidence: 99%
“…Indeed among all potential portals of entering the human body, the respiratory system is the most susceptible to particle invasion due to its large surface area in direct contact with the environment. 14 With their small size, a large portion of inhaled NPs can penetrate the respiratory tracts and deposit in the deep lung, where the NPs first interact with the pulmonary surfactant (PS) lining layer of alveoli and develop the so-called PS biomolecular corona. 15−17 The PS is composed of approximately 90% lipids, including various phospholipids and cholesterol, and 10% proteins (named SP-A, SP-B, SP-C, and SP-D) by weight.…”
Section: U Nderstanding Interactions Between Nanoparticlesmentioning
confidence: 99%
“…PM triggers pulmonary oxidative stress and inflammation by heterogeneous and complex mechanisms, with several responses according to different properties of PM particles. Indeed the ultrafine particles may directly enter cells via nonphagocytic pathways and then impair intracellular organelles like mitochondria (Mühlfeld C et al 2008); Ultrafine particulate has also been demonstrated to promote vascular calcification by activating NFKB signaling (Li R et al, 2013).…”
Section: Pathophysiological Mechanism Linking Particulate Matter (Pm)mentioning
confidence: 99%
“…In addition, up to 80% of PM, predominantly the coarse fraction, is able to enter pulmonary parenchyma by transcytosis through macrophages and alveolar epithelium cells. 44 These particles can access the pulmonary circulatory system and are subsequently adducted by plasma proteins. 44 As a consequence, the occurrence of these PM-protein complexes in pulmonary and systemic circulations can induce systemic immune responses, particularly in adipose tissue.…”
Section: Particulate Matter Causes Systemic Inflammationmentioning
confidence: 99%
“…44 These particles can access the pulmonary circulatory system and are subsequently adducted by plasma proteins. 44 As a consequence, the occurrence of these PM-protein complexes in pulmonary and systemic circulations can induce systemic immune responses, particularly in adipose tissue. 43,44 In summary, PM exposure is capable of triggering a complex immune response, which is initiated locally in the lung parenchyma and which subsequently activates systemic proinflammatory cascades (Figure 1).…”
Section: Particulate Matter Causes Systemic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation